2016
DOI: 10.3382/ps/pew069
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Synergistic effects of thymoquinone and curcumin on immune response and anti-viral activity against avian influenza virus (H9N2) in turkeys

Abstract: The main objective of this study was to determine the possible effects of thymoquinone (TQ) and curcumin (Cur) on immune-response and pathogenesis of H9N2 avian influenza virus (AIV) in turkeys. The experiment was performed on 75 non-vaccinated mixed-sex turkey poults, divided into 5 experimental groups (A, B, C, D, and E) of 15 birds each. Group A was kept as non-infected and a non-treated negative control (ctrl group) while group B was kept as infected and non-treated positive control (H9N2 group). Turkeys i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…The new curcumin derivative, tetrahydrocurcumin, was shown to be more active than curcumin in preventing the development of aberrant crypt foci and cell proliferation (Kim et al ., ,b; Chauhan, ). Furthermore, thymoquinone and curcumin have been shown to have a synergistic inhibitory effect on the influenza virus induced by increasing the efficiency of the immune response and this effect plays a significant role in diminishing the pathogenic effects of H9N2 in turkeys (Umar et al ., ). Curcumin was found to induce the activation of AMPK in human ovarian cancer cells (CaOV3 cells) in a time‐ and concentration‐dependent manner (~25–50 μM of curcumin; time: 15–120 min), as curcumin activated p38 phosphorylation that is an important downstream signal of AMPK, and elicited CaOV3 cell death (Pan et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The new curcumin derivative, tetrahydrocurcumin, was shown to be more active than curcumin in preventing the development of aberrant crypt foci and cell proliferation (Kim et al ., ,b; Chauhan, ). Furthermore, thymoquinone and curcumin have been shown to have a synergistic inhibitory effect on the influenza virus induced by increasing the efficiency of the immune response and this effect plays a significant role in diminishing the pathogenic effects of H9N2 in turkeys (Umar et al ., ). Curcumin was found to induce the activation of AMPK in human ovarian cancer cells (CaOV3 cells) in a time‐ and concentration‐dependent manner (~25–50 μM of curcumin; time: 15–120 min), as curcumin activated p38 phosphorylation that is an important downstream signal of AMPK, and elicited CaOV3 cell death (Pan et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Even the anti‐inflammatory ability of curcumin was well investigated, its anti‐IAV function studies are very limited. Umar et al . utilized turkeys to study the possible effects of curcumin on immuneresponse and pathogenesis of H9N2 avian influenza virus (AIV).…”
Section: Introductionmentioning
confidence: 99%
“…Umar et al 23 utilized turkeys to study the possible effects of curcumin on immuneresponse and pathogenesis of H9N2 avian influenza virus (AIV). They found that in cooperation with thymoquinone, curcumin could be able to dramatically improve the immune responses and restrain the pathogenesis of influenza viruses in turkeys.…”
Section: Introductionmentioning
confidence: 99%
“…is a plant in which the main active ingredient is curcumin. Several studies have shown that curcmin has an immunostimulatory effect;this can be proved by Umar et al's [2] study which gave curcumin in turkey feed. All groups were challenged with H9N2 Avian Influenza virus, and the treatment group showed mild clinical symptoms, the lowest viral shedding and higher titer than the control group.…”
Section: Introductionmentioning
confidence: 77%